Impact of Employee Resilience and Job Engagement on Project Success: Mediating role of Innovative Work Behavior - Iqbal, Muhammad Tayyab; Warraich, Imran Asghar; Haq, Saif Ul (Research Journal for Societal Issues, 2023)
This study aims to examine the impact of employee resilience and job engagement on project success, and the mediating role of innovative work behavior. The study draws on a sample of 170 from the population of 304 information technology (IT) companies in Lahore Pakistan to test the proposed hypotheses. Smart PLS statistical software has been used to calculate the structural modelling equation results for the subject study. The results indicate that both employee resilience and job engagement have a positive impact on project success. Furthermore, innovative work behavior partially mediates the relationship between employee resilience and project success, as well as between job engagement and project success. These findings highlight the importance of fostering employee resilience and job engagement to promote project success and the role of innovative work behavior in facilitating this relationship. Organizations can benefit from implementing strategies that enhance employee resilience and job engagement while promoting a culture of innovation to achieve project success.